Sharing Power : Lessons Learned from the Reform and Privatization of Moldova's Electricity Sector - Junge, Nils (World Bank: Washington, DC, 2013)
This study answers two questions about power sector reform in Moldova. First, did reform affect the poor and the non-poor differently? Second, are household consumption patterns different for private and public distribution networks? The study concludes that reforms have not disproportionately affected the poor. The gap in electricity consumption between poor and non-poor is closing, as a result of improvements in the supply of electricity, particularly in rural areas, and the significant growth in income over the past four years. Moldova's residential electricity consumption remains exceptionally low and is probably highly inelastic, especially for the very poor. This implies that unless they are accompanied by increases in income, future tariff increases could create large potential consumer welfare losses-as well as large revenue gains for the utility. It also implies that there may be room for substantial welfare gains by helping households better manage their electricity expenditures. Measures to do so could include introducing prepayment swipe cards for meters, in order to reduce both the costs and anxiety associated with disconnections; encouraging the poor to use more energy-efficient refrigeration and lighting technologies, through vouchers or other similar programs; and having the public sector defray the cost of extending access to clean, inexpensive gas in small towns where people rely on electricity for heating, if it can be done in a way that limits the financial liabilities for the government.